Psikoedukasi Mindfulness Untuk Mengatasi Empty Nest Syndrome Pada Lansia di Puskesmas Ulak Karang Selatan - Althafi Hilmanisa; Athifa Meriza Salsabila; Hikmatul Wazkia; Khairina Dwi Rivani; Mihalani Angelina Putri (PUSAKO : Jurnal Pengabdian Psikologi, 2022)
This research is motivated by the problem of empty cage syndrome (empty nest syndrome) which is defined as one of the common problems that occur from the transition or adjustment period to lonely situations and this is generally experienced by the elderly, where during this transition period a different pattern occurs. in parents, from being close and getting satisfaction with child care to having to live alone without the presence of children. The purpose of this study was to find out in depth about how the elderly face periods of loneliness or empty nest syndrome and appropriate efforts are made to reduce and prevent it. Respondents who participated in this study amounted to 9 elderly people who visited the Puskesmas Ulak Karang Selatan. This study uses a qualitative-descriptive method, to provide an overview of how the influence of mindfulness psychoeducation on empty nest syndrome in the elderly. The intervention method used is psychoeducation, by providing knowledge about empty nest syndrome and how to deal with it. Data were collected by interview and observation techniques. The results of this study, it was found that the elderly who experienced the nest-korong phase felt acceptance of the conditions experienced, received social support from fellow elderly and to reduce this feeling of loneliness the elderly filled their spare time with positive and beneficial activities for the elderly. Keywords: Psychoeducation, mindfulness, empty nest syndrome